Sistem Informasi Pelayanan Sosial Berbasis Web Pada Yayasan Penabulu STPI Provinsi Jambi - Alfadillah , Antrisa; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2022)
Yayasan Penabulu STPI Provinsi Jambi in social service still get trouble, such as : search for patient treatment data that takes time because they have to search one by one on the agenda book, sometimes there is a recording error recording patient treatment data, information about social services for TB and HIV is difficult to get the public because it has to go to a place directly to ask so it takes time, there is no website that can help health consultations for TB and HIV diseases online. The purpose of research is analyzing and system information design of social service using PHP programming language and MySQL database. Metodology of this research use prototype model and unified model language using use case diagram, activity diagram, and class diagram. Conclusion of this system can featuring drug data, outpatient data, prescription data, infomation data, forum data that is structured and display report necessary. Research advice are prototyped this system should be devised well and properly so that it will could be applied to Yayasan Penabulu STPI Provinsi Jambi.